Pengaruh Kebijakan Penurunan Jalur Merah terhadap Penerimaan Negara - Nurhidayati, Nurhidayati; Cahyani, Pramudita (Jurnal Ekonomi dan Pembangunan Indonesia, 2020)
The decrease of customs clearance time is a form of reform and modernization of customs, through the policy of red line reduction. With a short customs clearance time, the velocity of goods in ports and airports become faster so as to support the smooth flow of national logistics. Smooth flow of goods will support the trade, which ultimately government revenue from import duties will be affected. This study aims to find the effect of the policy on the government revenue. The study used the data of 35 periods before and after the red line reduction policy was taken. The result shows that the policy of red line reduction negatively affects the government revenue of import duties.